2019
DOI: 10.1007/s00213-019-05228-w
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of alcohol use in the structure and neurochemistry of insular cortex: a correlational study

Abstract: Rationale Insular cortex supports the representation of motivational feelings through the integration of interoceptive information concerning bodily physiology. Compromised insular integrity is implicated in alcohol and drug use disorders. Alcohol-associated insular dysfunction may arise through aberrant glutamatergic neurotransmission associated with selective neuronal death and atrophy. Objective In a sample of alcohol users, we combined magnetic resonance spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 83 publications
(102 reference statements)
1
7
0
Order By: Relevance
“…It has been proposed that the insula and the anterior cingulate cortex form the salience network (SN), that coordinates between the default mode network (DMN) and the central executive network (CEN) 50 . In our study we found lower volume of the insula, a region whose morphology has been associated with substance use compulsion and severity 51 . The insula plays a major role in interoception by integrating information from the internal physiological state, and projecting information to the ACC, ventral striatum and prefrontal cortex to initiate adaptive responses 52 .…”
Section: Discussionsupporting
confidence: 59%
“…It has been proposed that the insula and the anterior cingulate cortex form the salience network (SN), that coordinates between the default mode network (DMN) and the central executive network (CEN) 50 . In our study we found lower volume of the insula, a region whose morphology has been associated with substance use compulsion and severity 51 . The insula plays a major role in interoception by integrating information from the internal physiological state, and projecting information to the ACC, ventral striatum and prefrontal cortex to initiate adaptive responses 52 .…”
Section: Discussionsupporting
confidence: 59%
“…Additionally, high alexithymia scores predict earlier age of alcohol use onset, longer duration of alcohol misuse, and increased amount of alcohol consumed ( Kopera et al, 2015 ). Correspondingly, high alexithymia scores, together with impulsivity, predict heavy alcohol drinking among university students ( Betka et al, 2019 , Lyvers et al, 2019 ). Thus, alexithymia may specifically increase the risk of developing AUD ( Cruise and Becerra, 2018 , Uzun et al, 2003 ).…”
Section: Introductionmentioning
confidence: 98%
“…Together these findings suggest that insular activity is down-regulated during abstinence and abstinenceassociated negative affective states in individuals with alcohol use disorder. From a mechanistic perspective, compulsive alcohol use reduces insular glutamate-glutamine concentrations suggesting that perhaps an excitatory insular pathway may be driving this behaviour (Betka et al, 2019). Additionally, Laukkanen et al (Laukkanen et al, 2019) showed increased [ 3 H]quisqualic acid binding (a group I mGlu receptor agonist) in post-mortem anterior insular cortex brain tissue of individuals with alcohol use disorder compared to control brains.…”
Section: The Role Of the Anterior Insular Cortex In Alcohol Use Disordermentioning
confidence: 99%
“…Indeed, the insular has connections with the ventral striatum, particularly the nucleus accumbens core, and the ventral tegmental area/ substantia nigra (Allen et al, 1991;Ohara et al, 2003;Wright & Groenewegen, 1996). Importantly, dopamine, gamma-aminobutyric acid (GABA) and glutamate appear to be key neurotransmitters involved in the function of the insular cortex (Betka et al, 2019;Ohara et al, 2003). One class of disorders where motivated behaviours are augmented include substance use disorders.…”
mentioning
confidence: 99%